Strategi Komunikasi Kesehatan Paramedis dalam Mengurangi Stunting pada Anak di Desa Unteboang Tapanuli Tengah - Tarihoran, Yuli Kartika; Ritonga, Syafruddin; Khairullah, Khairullah (Universitas Medan Area, 2025)
Based on this study, the health communication strategy by paramedics in Unteboang Village in an effort to reduce stunting rates has been carried out through health counseling and posyandu activities. However, its effectiveness is still constrained by low community participation, parental resistance to stunting diagnosis, and limited access to comprehensive information. A qualitative approach with a descriptive method is used in this study to analyze the communication strategies applied, with data collection techniques in the form of interviews, observations, and documentation studies. The results of the study show that the wider use of communication media, such as digital and print media, as well as a more adaptive interpersonal approach, is needed to increase public awareness of the importance of stunting prevention. Therefore, there is a need for innovation in health communication strategies, including increasing the role of health cadres, the use of digital technology, and cooperation with community leaders. With a more inclusive approach and periodic evaluation, it is hoped that the effectiveness of health communication can be improved to create more positive behavior change in stunting prevention and management.